Formulasi dan uji aktivitas antioksidan sediaan sheet mask dari sari buah lemon cui (Citrus microcarpha B.) sebagai anti-aging - Arifin, Arfiani; Nada, Salsabila Yudratun; Mawarni, Razifah Suci; Adi, Abdul Vashar (Universitas Mataram, 2024)
Lemon cui (Citrus microcarpa Bunge.), also known as fish lemon or kalamansi lemon, is a local citrus that mainly grows in North Sulawesi. This study aims to determine the IC50 value of lemon cui juice and develop